2016
DOI: 10.1177/1076029616639704
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Matrix Metalloproteinases in Arthroplasty Patients and Their Correlation With Inflammatory and Thrombotic Activation Processes

Abstract: An imbalance of matrix metalloproteinases (MMPs) and their inhibitors is thought to play a major role in the pathophysiology of joint diseases. The aim of this study is to provide additional insights into the relevance of MMP levels in arthroplasty patients in relation to inflammation and thrombosis. Deidentified plasma samples from 100 patients undergoing total hip arthroplasty or total knee arthroplasty were collected preoperatively, on postoperative day 1, and on postoperative day 3. Tissue inhibitor of MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Previous studies examining MDEs and their relevance to the pathogenesis of DJD have shown results consistent with those that have been observed here. 1921 These findings, in addition to previous data, provide evidence that patients with DJD have intrinsic abnormalities that may contribute to the pathogenesis of DJD. Although the popular belief that mechanical loading and shear force on weight-bearing joints is the major contributor to OA, the results of this study support the hypothesis that alterations in the levels of MDEs coupled with the changes in joint lubrication may contribute to osteoarthritic disease progression.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies examining MDEs and their relevance to the pathogenesis of DJD have shown results consistent with those that have been observed here. 1921 These findings, in addition to previous data, provide evidence that patients with DJD have intrinsic abnormalities that may contribute to the pathogenesis of DJD. Although the popular belief that mechanical loading and shear force on weight-bearing joints is the major contributor to OA, the results of this study support the hypothesis that alterations in the levels of MDEs coupled with the changes in joint lubrication may contribute to osteoarthritic disease progression.…”
Section: Discussionsupporting
confidence: 75%
“…In AAD, blood flow enters into the media of aorta through the tear of the intima, activating the coagulation system, thrombosing in false lumen, subsequently fibrin degrading and releasing D-dimer into the blood circulation [ 29 ]. Recently, it is reported that D-dimer can play a potential role in activating MMPs [ 30 ]. Thus, vinculin and D-dimer may both anticipate the pathophysiology of tissue degradation during AAD via the pathway of MMPs, which is exactly the further investigation purpose in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis demonstrated that D-dimer was a useful screening tool for excluding AAD [ 37 ]. Alexander et al found no significant relationship between MMP9 and D-dimer in arthroplasty patients [ 38 ], while Pastorelli et al showed a positive correlation of serum TLR4 with D-dimer in inflammatory bowel diseases [ 39 ]. Moreover, Giachino et al proved that serum MMP9 was significantly correlated with both CRP and D-dimer in patients with AAD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%